Flutuação populacional de Meloidogyne enterolobii em pomar de goiabeira (Psidium guajava) - Almeida, Eduardo J.; Santos, Jaime M.; Martins, Antonio B.G. (My University, 2010)
The objective of this work was to study the population fluctuation of Meloidogyne enterolobii in a commercial orchard of 'Paluma' guava with five years of age, under micro sprinkler irrigation system and usual practices for this crop. In the orchard, located in the municipality of Vista Alegre do Alto (SP) Brazil and infested by M. enterolobii, five plants exhibiting nematode symptoms were selected for monthly sampling from July 2007 to June 2008. Two single samples of rhizosphere soil and guava roots were collected from each plant, with the aid of hoe to a depth of 20 cm on the projection of the trees, forming a composite sample per plant. In nematology laboratory of Faculdade de Ciencias Agrarias e Veterinarias Universidade Estadual Paulista, eggs and second stage juveniles (J2) of M. enterolobii were extracted from the samples and quantified. There was not a marked seasonal variation in the nematode population in soil or roots, possibly as a result of the guava vegetation stimulated by irrigation or the presence of invasive plants during the experimental period. However, the soil density reached a peak in January, corresponding to the month of elevated rainfall and temperatures. In roots, there were two significant peaks, in February and a major peak in August. There was a negative correlation between nematode populations in soil and roots.
Population fluctuation of Meloidogyne enterolobii in guava (Psidium guajava) orchard.